PENGARUH STRATEGI PEMBELAJARAN DAN PERCAYA DIRI TERHADAP KREATIVITAS GERAK SISWA KELAS III SD - Mohamad Syarif Sumantri; Eneng Kurnia (Universitas Negeri Malang, 2015)
Abstract: The current study was intended to analyze the effect of teaching and learning strategies as well as the self-concept towards the motion creativity learning outcome of the third graders of elementary schools. The study utilized experimental method with 2 x 2 factorial design. By using random sampling technique, 32 students were chosen as the samples. The results of the study suggested that (1) there was score of motion creativity between the students who joined the inductive strategy from those who joined the deductive strategy, (2) students who had high self-concept performed better motion creativity when they joined inductive strategy, (3) students who had low self-concept performed better motion creativity when they joined deductive strategy, (4) there was an interaction effect of teaching and learning strategies as well as the self-concept towards the motion creativity learning outcome of the third graders of elementary schools.Abstrak: Penelitian ini bertujuan mengkaji pengaruh strategi pembelajaran dan konsep diri terhadap hasil belajar kreatvitas gerak siswa kelas III SD. Penelitian mengunakan metode eksperimen dengan desain factorial 2 x 2. Teknik sampling acak sederhana dengan sample 32 siswa. Hasil penelitian (1) terdapat skor dari kreativitas gerak antara siswa yang mengikuti dengan strategi induktif dengan strategi deduktif, (2) siswa yang memiliki konsep diri tinggi menunjukan hasil belajar kreatifitas gerak lebih baik dari pada strategi pembelajaran induktif, (3) siswa yang memiliki konsep diri rendah memiliki skor lebih tinggi dengan strategi deduktif, (4) terdapat pengaruh interaksi antara strategi pembelajaran dan konsep diri terhadap hasil belajar kreativitas gerak siswa kelas III SD.